Beyond September 11th : an anthology of dissent - Scraton, Phil (Pluto Press, 2002)
The unprecedented and tragic events in New York, Washington and Pennsylvania left an indelible mark on world politics. Civilian deaths in horrific circumstances triggered an uncompromising response from the US administration and its allies: an open-ended "war on terrorism". This anthology includes some of the world's leading commentators - Noam Chomsky, Robert Fisk, Naomi Klein, John Pilger and A. Sivanandan. This book presents accessible, detailed and often deeply personal accounts of the aftermath, the bombing of Afghanistan and the dubious claims for its legality. From investigative journalists to critical academics, human rights lawyers and anti-racist campaigners, the contributors are united in their opposition to military intervention in Afghanistan and beyond and to the attack on civil liberties in the US, the UK and Europe. From the US and Canada, Herman and Julia Schwendinger, Jonathan Farley, Tony Platt, Cecilia O'Leary, Christian Parenti and Michael Mandel are among those from academia who question the validity, lawfulness and political consequences of the Bush/Blair agenda. Examining the context and rhetoric of US vengeance - ennobled by the symbolic title "Enduring Freedom"--The contributors challenge political and popular definitions, constructions, pathologization and reporting of terrorism. In questioning the representation of war as "just", the anthology focuses on civilian deaths in Afghanistan, evidence of US/allied atrocities, violations of prisoners' rights and US determination to escalate military offensives regardless of global destabilization.